PERBEDAAN KEMAMPUAN KONEKSI MATEMATIS MAHASISWA TATALAKSANA BERDASARKAN GAYA BELAJAR MENGGUNAKAN BLENDED LEARNING - Supriyanta Supriyanta; Joko Tri Haryanta (Akademi Pelayaran Nasional Surakarta, 2022)
Arif, Widarti. 2013. Kemampuan Koneksi Matematis Dalam menyelesaikan Masalah Kontektual ditinjau dari Kemampuan Matematis Siswa, Jurnal Stkip Pgri Jombang. Vol 1, No. 003 Tahun 2013 (diakses tanggal 18 Nopember 2016.Ayla, Arseven. 2015. Mathematical Modelling Approach in Mathematics Education Faculty of Education, Cumhuriyet University, Turkey. Universal Journal of Educational Research 3(12): 973-980, 2015 http://www.hrpub.org DOI: 10.13189/ujer.2015.031204 .Astuti, D.A., Novita, D. 2019. Blended Learning Terhadap Kemampuan Komunikasi Matematis. Iprosiding Sendika:Vol 5, No 1. 2019.Burkhardt, H. 2006. Modelling in mathematics classrooms: reflections on past developments and the future. ZDM, 38(2), 178–195. http://dx.doi.org/10.1007/ BF02655888.Chris, Hurst .2007. Numeracy in Action: Students Connecting Mathematical Knowledge to a Range of Contexts Mathematics: Essential Research, Essential Practice - Volume 1Depaepe, F., De Corte, E., & Verschaffel, L. 2010. Teachers’ approaches towards word problem solving: elaborating or restricting the problem context. Teaching and Teacher Education, 26(2), 152–160. http://dx.doi.org/10.1016/j. tate.2009.03.016.Dedi, Rohendi; Jojon, Dulpaja. 2013. Connected Mathematics Project (CMP) Model Based on Presentation Media to the Mathematical Connection Ability of Junior High School Student. Journal of Education and Practice. www.iiste.org ISSN 2222-1735 (Paper) ISSN 2222-288X (Online) Vol.4, No.4, 2013.Dixon, Tara & Martin, O. 2012. Communication Skill. (online). http://www.practicebasedlearning.org.Elliot, M. 2002. Blended Learning:The Magic Is In The Mix. In A. Rossett (ed). The ASTD e-learning Handbook (pp.58-63). New York: McGraw-Hill.Frankenstein, M. 2009. Developing a criticalmathematical numeracy through real real-life word problems. In L. Verschaffel, B. Greer, W. V. Dooren, & S. Mukhopadhyay (Eds.), Words and worlds _ modelling verbal descriptions of situations (pp. 111–130).Rotterdam, the Netherlands: Sense.Gökhan, Karakoç and Cengiz, Alacacı. 2015. Real World Connections in High School Mathematics Curriculum and Teaching. Turkish Journal of Computer and Mathematics Education Vol.6 No.1 (2015), 31-46.Hadi, Sutarto. 2005. Pendidikan Matematika Realistik dan Implementasinya. Banjarmasin: Penerbit Tulip.Herdiaan. 2010. Kemampuan Komunikasi Matematika (Online) https://herdy07.wordpress.com/2010/05/27/kemampuan-koneksi-matematik-mahasiswa/ (diakses tanggal 23 Nopember 2016)Hoogland, K., & Stelwagen, R. 2011. A new Dutch numeracy framework. In T. Maguire, J. J. Keogh, & J. O’Donoghue (Eds.), Mathematical Eyes: a Bridge Between Adults, the World and Mathematics. Proceedings of the 18th International Conference of Adults Learning Mathematics—a Research Forum (ALM) (pp. 193– 202).Tallaght, Ireland: ITT. Hoogland, K., & De Koning, J. 2013. Rekenen in Beeld [Images of numeracy]. Utrecht, the Netherlands: DANS. http://dx.doi.org/10.17026/dans-za6-5q6c. Hoogland, K., De Koning J., Bakker, A., Pepin, B., Gravemeijer K., 2016. Descriptive versus depictive representation of reality in contextual mathematical problems: the effect on students’ performances. (submitted).Johnson, D.W, & Johnson, R .1978. Comperative, Competitive, and Individualistic Learning. Journal of Research and Development in Education, 12. p. 8-15.Judith, Mousley. 2004. An Aspect Of Mathematical Understanding: The Notion Of “Connected Knowing Proceedings of the 28th Conference of the International Group for the Psychology of Mathematics Education, 2004 Vol 3 pp 377–384.Kaiser, G., Blomhøj, M., & Sriraman, B. 2006. Towards a didactical theory for mathematical modelling. ZDM, 38(2), 82–85. http://dx.doi.org/10.1007/ BF02655882. Lave, J. 1992. Word problems: a microcosm of theories of learning. In P. Light, & G. Butterworth (Eds.), Context and cognition: ways of learning and knowing (pp. 74– 92). New York, NY: Harvester Wheatsheaf.NCTM. 2000. Principle and Standars for School Mathematic. Virginia. NCTMPalm, T. 2009. Theory of authentic task situations. In L. Verschaffel, B. Greer, W. V. Dooren, & S. Mukhopadhyay (Eds.), Words and worlds _ modelling verbal descriptions of situations (pp. 3–20).Rotterdam, the Netherlands: Sense.Reusser, K. & Stebler, R. 1997. Every word problem has a solution: the suspension of reality and sense-making in the culture of school mathematics. Learning and Instruction, 7(4), 309–327. http://dx.doi.org/10.1016/s0959-4752(97)00014-5.Sagala, Syaiful. 2011. Konsep dan Makna Pembelajaran. Bandung. Alfabeta.Schnotz, W. 2005. An integrated model of text and picture comprehension. In R. E. Mayer (Ed.), The Cambridge handbook of multimedia learning (pp. 31–48). Cambridge, UK: Cambridge University Press.Schnotz, W., Baadte, C., Müller, A., & Rasch, R. 2010. Creative thinking and problem solving with depictive and descriptive representations. In L. Verschaffel, E. De Corte, T. De Jong, & J. Elen (Eds.), Use of Representations in Reasoning and Problem Solving – Analysis and Improvement (pp. 11–35). London, UK: Routledge.Sugiman. 2008. Koneksi Matematik Dalam Pembelajaran Matematika Di Sekolah Menengah Pertama. Jurnal Pythagoras Vol. 4, No. 1, Juni 2008: 5666 (diakses tanggal 18 Nopember 2016).Sugiono, 2015, Metode Penelitian Manejemen. Bandung. Alfabeta.Sugiono, 2015, Statistik Nonparametris Untuk Penelitian. Bandung. AlfabetaSugiono, 2016, Metode Penelitian Kombinasi (Mixed Methods). Bandung. Alfabeta. Yani, Ramdani. 2012. Pengembangan Instrumen Dan Bahan Ajar Untuk Meningkatkan Kemampuan Komunikasi, Penalaran, Dan Koneksi Matematis Dalam Konsep Integral. Jurnal Penelitian Pendidikan Vol. 13 No. 1, April 2012 (diakses tanggal 18 Nopember 2016). Zevenbergen, R., & Zevenbergen, K. 2009. The numeracies of boatbuilding: new numeracies shaped by workplace technologies. International Journal of Science and Mathematics Education, 7(1), 183–206. http://dx.doi.org/10.1007/s10763- 007-9104-9.